Christianity, tolerance, and pluralism : a theological engagement with Isaiah Berlin's social theory - Jinkins, Michael, 1953- (Routledge studies in religion ;, 2004)
This book provides a sustained, critical and theological engagement with arguably the most crucial aspect of contemporary society - its diversity. The author finds in the social theory of Isaiah Berlin a number of fruitful ways to reframe the debate over these questions, and to contribute to a more positive conversation regarding our fundamental differences. The book focuses particularly on Berlin's critique of monism and idealistic utopianism, arguing that pluralism does not represent a failure in the nature of human society, but a superabundance of possibilities in a created world gr.